Numerical and Experimental Simulation of the B-jump in an Abrupt Roughened Bed of a Stilling Basin - M.J N; M. SH; S.M K; M. F (مهندسی منابع آب, 2014)
Hydraulic jump type stilling basins with abrupt drop are used to reduce the basin length and to ensure the start of jump at the front of basin immediately downstream of gates. In this type of basin, four different types of jumps can develop of which the most occurred type is the B-jump. On the other hand, it has been shown that the bed roughness can reduce both of the jump length and the required tail-water depth too. Therefore, in the present study, the B-jump in a roughened bed of an abrupt drop basin was simulated by the three dimensional numerical model of Flow-3D and the results are compared with experimental data. The characteristics of B-jump in a roughened bed such as sequent depth, flow velocity distribution, and bed shear stress were obtained from both numerical and experimental models and compared. For numerical simulation of the B-jump, the method of control volume in free surface water and the RNG k-ε turbulent model were applied. The results show that the RNG k-ε is a better simulation than the k-ε turbulent model. The results of both numerical and experimental models proved that for the B-jump in a roughened bed stilling basin, the sequent depth reduces, which can be due to roughness and an increase in the bed shear stress, as a result of both the bed and the abrupt drop.